Excisional haemorrhoidectomy: is it safe in patients with an ileal pouch–anal anastomosis?. (24th February 2020) - Lightner, A. L.; Kearney, D.; Giugliano, D.; Hull, T.; Holubar, S.; Shawki, S.; Steele, S. R.
Abstract: Aim: Excisional haemorrhoidectomy in patients with ulcerative colitis (UC), especially those undergoing an ileal pouch–anal anastomosis (IPAA), remains controversial. The aim of our study was to determine the safety of excisional haemorrhoidectomy in UC patients with and without an IPAA. Method: A retrospective review of all adult UC patients undergoing excisional haemorrhoidectomy between 1 January 1995 and 1 January 2019 at a tertiary inflammatory bowel disease referral centre was performed. Data collected included patient demographics, clinical characteristics of UC, prior surgical intervention for UC (colectomy, IPAA) and complications after haemorrhoidectomy. Results: Forty‐one adult patients [50% male; median age 52 (range 25–79) years] with UC underwent excisional haemorrhoidectomy between 1 January 1995 and 1 January 2019. The majority ( n = 23) had not previously undergone surgery for UC. However, eight had already undergone construction of an IPAA at the time of haemorrhoidectomy, seven had IPAA at the time of haemorrhoidectomy and three had an IPAA constructed subsequent to haemorrhoidectomy. Two (4.9%) patients need to go back to theatre for postoperative bleeding. There were no further 30‐day complications or long‐term nonhealing of the surgical site. There were no pouch complications in those who had haemorrhoidectomy at the time of IPAA construction or in the presence of an IPAA. Conclusion: Our data suggest that excisional haemorrhoidectomy may be performed safely in carefully selected UC patients with symptomatic haemorrhoids with or without IPAA and even at the time of IPAA construction.